Consequences of leniency programmes and whistleblowing measures for the sanctioning process in criminal proceedings - Kert, Robert (European Integration Studies, 2025)
Whistleblowing and leniency programmes are important instruments to detect and successfully solve crimes. Whereas whistleblowers are natural persons who report or disclose legal violations in which they are not necessarily involved, principal witnesses are involved in criminal activities and report their knowledge to the authorities. Legal systems must provide incentives for people to report their knowledge and make it available to the authorities. Whistleblowers must therefore be guaranteed adequate protection, and principal witnesses must benefit from disclosing their knowledge by having their penalties reduced or waived entirely.